2023
DOI: 10.1002/bio.4528
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric mechanoluminescence in single Pr3+‐activated LiGa5O8

Abstract: Mechanoluminescence (ML) materials have found potential applications in information storage, anti‐counterfeiting, and stress sensing. Conventional stress sensing based on absolute ML intensity is prone to significant mistakes owing to the unpredictability of measurement surroundings. However, implementing a ratiometric ML sensing technique may considerably ameliorate this issue. In this study, a single activator‐doped gallate material (LiGa5O8:Pr3+) is proposed to determine the relationship between the ML inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Consequently, it can make the fabric appear much whiter and brighter, which is called photoluminescence (PL) whitening. Moreover, it has been found that without any preirradiation, some materials such as ZnS: Cu/Mn 2+ can emit intense light under mechanical stimuli, including friction, stretching, compression, or impact, and their brightness is quantitatively related to the applied stress, which is called mechanoluminescence (ML) sensing. Accordingly, the PL whitening and ML sensing materials can utilize natural sunlight or ubiquitous mechanical energy in daily life to generate light emissions, avoiding the requirement of an artificial irradiation source. Therefore, these materials show great advantages in energy conservation and environmental protection. However, the PL whitening and ML sensing effects have never been simultaneously observed in a single material.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it can make the fabric appear much whiter and brighter, which is called photoluminescence (PL) whitening. Moreover, it has been found that without any preirradiation, some materials such as ZnS: Cu/Mn 2+ can emit intense light under mechanical stimuli, including friction, stretching, compression, or impact, and their brightness is quantitatively related to the applied stress, which is called mechanoluminescence (ML) sensing. Accordingly, the PL whitening and ML sensing materials can utilize natural sunlight or ubiquitous mechanical energy in daily life to generate light emissions, avoiding the requirement of an artificial irradiation source. Therefore, these materials show great advantages in energy conservation and environmental protection. However, the PL whitening and ML sensing effects have never been simultaneously observed in a single material.…”
Section: Introductionmentioning
confidence: 99%
“…The spinel-like structured and crystalline matrix of LiGa 5 O 8 can be doped with various rare earth and transition metal ions, which impart the desired NIR luminescence upon excitation. These doped phosphors exhibit sharp emission lines characteristic of the f – f or d – d transitions of the activator ions in six-coordination sites such as Cr 3+ , Ni 2+ , Tm 3+ , and Pr 3+ . Recent literature highlights the occurrence of energy transfer between Cr 3+ (broadband emission) and Ni 2+ (broadband emission) . However, the mechanism underlying the energy transfer from sharp-band to broadband emission remains inadequately addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The study of persistent luminescence in lithium gallate has also been explored. Wu et al 17 studied the mechano-luminescence properties of Pr 3+ -doped lithium gallate, finding it suitable for stress sensing. They assessed its reliability under various conditions, such as varying force, sample content, and thickness.…”
Section: Introductionmentioning
confidence: 99%